2020
DOI: 10.3390/microorganisms8040463
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary In Vitro Studies on Corynebacterium urealyticum Pathogenetic Mechanisms, a Possible Candidate for Chronic Idiopathic Prostatitis?

Abstract: Corynebacterium urealyticum is a well-known opportunistic uropathogen that can occur with cystitis, pyelonephritis, and urinary sepsis. Although a wide variety of coryneform bacteria have been found from the male genital tract of prostatitis patients, only one clinical case of prostatitis caused by C. urealyticum has been reported. The aim of this study was to evaluate the in vitro tropism of C. urealyticum towards LNCaP (lymph node carcinoma of the prostate) human cells line and the influence of acetohydroxam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition, Corynebacterium is a group of Gram‐positive bacteria and is frequently categorized as opportunistic pathogens (Luo et al, 2022). C. urealyticum is a well‐known opportunistic uropathogen involved in bacteremia, cystitis, and pyelonephritis (Nicolosi et al, 2020; Salem et al, 2015). Notably, Pan et al (2020) found that Corynebacterium was increased in rats with hyperuricemic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Corynebacterium is a group of Gram‐positive bacteria and is frequently categorized as opportunistic pathogens (Luo et al, 2022). C. urealyticum is a well‐known opportunistic uropathogen involved in bacteremia, cystitis, and pyelonephritis (Nicolosi et al, 2020; Salem et al, 2015). Notably, Pan et al (2020) found that Corynebacterium was increased in rats with hyperuricemic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, pulmonary infections by this microorganism that spread through the hematogenous route can reach the prostate causing chronic prostatitis [ 29 ]. The particularities in the microbial culture have made the accurate diagnosis of genitourinary infections difficult, as in Corynebacterium urealyticum , a Gram-positive, facultative anaerobic bacillus that is difficult to grow, responsible for prostatitis that is also associated with calcifications in the prostate [ 30 ]. Molecular tools allow the diagnosis of hidden infections in the light of traditional microbiological culture techniques.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaT cell viability alone and inoculated with BEV (10 ng per well), HAc40 c40, and HA BEV-treated and alone was evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrasodium bromide (MTT) assay. Tests were performed as previously described with modifications [ 33 ]. Briefly, HaCaT cells were seeded in 96-well plates at a density of 1.5 × 104 per well and incubated overnight at 37 °C before experiments.…”
Section: Methodsmentioning
confidence: 99%